In Vitro Antioxidant Activity of Litsea martabanica Root Extract and Its Hepatoprotective Effect on Chlorpyrifos-Induced Toxicity in Rats - Phraepakaporn Kunnaja; Sunee Chansakaow; Absorn Wittayapraparat; Pedcharada Yusuk; Seewaboon Sireeratawong (Molecules, 2021)
In Thailand, people in the highland communities whose occupational exposure to pesticides used the root of Litsea martabanica as a detoxifying agent. However, the scientific data to support the traditional use of this plant are insufficient. This study aimed to evaluate the antioxidant activity and anti-pesticide potential of L. martabanica root extract. Antioxidant properties were investigated by 2,2′-diphenyl-1-picrylhydrazyl (DPPH) assay, superoxide radicals scavenging assay, 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay, ferric reducing antioxidant power (FRAP), and total phenolic content determination. In all assays, L. martabanica extracts and their fractions exhibited high antioxidant activities differently. The water extract is traditionally used as a detoxifying agent. Therefore, it was chosen for in vivo experiments. The rats received the extract in a way that mimics the traditional methods of tribal communities followed by chlorpyrifos for 16 days. The results showed that acetylcholinesterase activity decreases in pesticide-exposed rats. Treatment with the extract caused increasing acetylcholinesterase activity in the rats. Therefore, L. martabanica extract may potentially be used as a detoxifying agent, especially for the chlorpyrifos pesticide. The antioxidant properties of L. martabanica may provide a beneficial effect by protecting liver cells from damage caused by free radicals. Histopathology results revealed no liver cell necrosis and showed the regeneration of liver cells in the treatment group. L. martabanica extract did not cause changes in behavior, liver weight, hematological and biochemical profiles of the rats.